Strengthening Moral Action Through Global Citizenship Education In Elementary School - Daryati, Daryati; Triyanto, Triyanto; Tarsidi, Deni Zein (Universitas Sebelas Maret, 2025)
In the current era of globalization, global citizenship education is important for the younger generation, where currently there are many moral crises, especially in terms of moral actions. This study aims to review the literature related to the instillation of global citizenship education values in elementary schools to strengthen moral actions. The research method used in this study is the SLR (Systematic Literature Review) method. Data collection was obtained by documenting related articles on similar research in the last 7 years. Articles obtained and used in this study were 20 accredited national and international journal articles obtained from Google Scholar. The results of the analysis show that the instillation of global citizenship education values. through global competencies in the cognitive, socio-emotional and behavioral dimensions will equip students with skills and real actions as active and responsible global citizens who will be able to strengthen moral actions. Thus, it is concluded that in learning, students are expected to have understanding, empathy and life skills in the 21st century, such as being able to think critically, creatively, the ability to solve global issues and be able to face various challenges that will be faced in the era of technological and information advancements that are realized through real moral actions.